Arctic indigenous youth resilience and vulnerability: Comparative analysis of adolescent experiences across five circumpolar communities. (October 2014) - Ulturgasheva, Olga; Rasmus, Stacy; Wexler, Lisa; Nystad, Kristine; Kral, Michael
Arctic peoples today find themselves on the front line of rapid environmental change brought about by globalizing forces, shifting climates, and destabilizing physical conditions. The weather is not the only thing undergoing rapid change here. Social climates are intrinsically connected to physical climates, and changes within each have profound effects on the daily life, health, and well-being of circumpolar indigenous peoples. This paper describes a collaborative effort between university researchers and community members from five indigenous communities in the circumpolar north aimed at comparing the experiences of indigenous Arctic youth in order to come up with a shared model of indigenous youth resilience. The discussion introduces a sliding scale model that emerged from the comparative data analysis. It illustrates how a "sliding scale" of resilience captures the inherent dynamism of youth strategies for "doing well" and what forces represent positive and negative influences that slide towards either personal and communal resilience or vulnerability. The model of the sliding scale is designed to reflect the contingency and interdependence of resilience and vulnerability and their fluctuations between lowest and highest points based on timing, local situation, larger context, and meaning.